Leisure and health education: methodological report of distance education during the Covid-19 pandemic (Research, Society and Development, 2020)
The objective of this work was to report the methodology used for teaching Physical Conditioning Gymnastics (GCF) during the Covid-19 Pandemic through Information and Communication Technologies (ICT) in the final years of a public school. The purpose was to contribute to the promotion of health and quality of life (QOL) during the students' active leisure. It is a qualitative study, with a descriptive characteristic, classified as an experience report. The report is about the application of a teaching methodology in the modality of Distance Education (DE) using the resources of ICT, mainly Google Classroom in the teaching of Gymnastics. The research was carried out in three stages: Literature review; Production of teaching material on GCF; Pedagogical intervention in distance education. The teaching tools used in this study were: Google Classroom; Google Meet and WhatsApp. They proved to be suitable for the GCF teaching process during social isolation.